Compositional Changes in Colostrum and Milk of Hill Cows of Uttarakhand During Different Lactation Stages - PATOO, R. A.; SINGH, D. V.; RUKSHAN, RUKSHAN; KAUSHL, S.; SINGH, M. K. (Indian Journal of Hill Farming, 2015)
Present study was undertaken to determine the composition al changes in colostrum and milk of Hill cow of Uttarakhand during different stages of lactation period. Fifteen colostrum samples per day were collected during first five postpartum days while as six milk samples of Hill cows were collected at fortnightly interval up to 36 weeks of lactation period and were subjected to various physicochemical analyses. Maximum mean fat, protein, total solid, ash per cent, and electric conductivity in colostrum of Hill cow was observed on first postpartum days as 6.79±0.16, 13.28±0.13, 23.02±0.27, 1.10±0.06 and 3.41±0.23, respectively and later on decreased as postpartum days advances. But lactose per cent and pH showed an increasing trend during first five postpartum days. In milk of Hill cows minimum mean fat (4.26±0.39 %), protein (3.37±0.50 %) and total solids (12.78±0.42 %) per cent were observed in III, VII and IX stage of lactation, respectively and showed an increasing trend as lactation advances. While as maximum mean lactose (4.62±0.51 %) per cent was observed in III stage of lactation and decreased during last stage of lactation. It can be concluded that colostrum of Hill cow was richer in fat, protein, lactose, total solids and ash content as while as its milk had higher content of fat, protein, SNF, total solids and lower pH, electric conductivity and somatic cell count.